Selenium in Hyperthyroidism - Shiela Stefani; Lukman Halim; Diyah Eka Andayani; Fiastuti Witjaksono (World Nutrition Journal, 2020)
Introduction: Thyroid gland has the highest selenium content compare with other endocrine organs. Enzyme that catalyzing thyroid hormone activation, iodothyronine deiodinases, were identified as selenocysteine-containing proteins. Selenium levels in soil and rice consumed in Indonesia were lower than in several other countries, which can increase the risk of selenium deficiency.Methods: This is an article review of the current literatures published up to November 2018 about the role of selenium in hyperthyroid.Result: Several studies have shown that selenium supplementation can be beneficial in patients with Graves disease and autoimmune thyroiditis. Selenium has an important immunomodulatory effect, but the effects of selenium supplementation in hyperthyroid has not been conclude. Data regarding selenium intake, prevalence of deficiency, and the relationship between selenium and thyroid disease in Indonesia are limited. Various studies of selenium supplementation in thyroid disease provide controversial results, so there are no guidelines that include selenium as standard therapy hyperthyroid. Selenium supplementation can enhance the restoration of biochemical euthyroidism in Graves disease and was associated with a significant decrease in the levels of thyroid peroxidase antibodies in autoimmune thyroiditis.Conclusions: Micronutrients that play a role in thyroid hormone synthesis and maintain thyroid function in addition to selenium are iodine, iron, zinc, and vitamin A. By correcting the deficit of selenium, and meeting other micronutrient requirements may provide health benefits in patient with hyperthyroid.